Investigating the Lived Experiences of Abused Mothers: A Phenomenological Study - Zabihollah Abbaspour; Golshan Vasel; Reza Khojastehmehr (Kerman University of Medical Sciences, 2021)
Introduction: Domestic/family violence including child abuse, spousal abuse, elder abuse, and parental abuse is a common issue in the modern world. Adolescent-to-mother abuse is one of the phenomena that have been the focus of attention in recent decades due to its negative effects on the family system. The objective of the present study was to investigate the lived experiences of mothers abused by their adolescent children and to determine its final structure by surveying the research participants. Methods: This study employed a qualitative and phenomenological method. Nine participants were selected using the purposive sampling method and in-depth interviews were conducted until data saturation. The interviews were recorded and transcribed and then analyzed using a descriptive phenomenological psychological method. Results: Data analysis revealed 11 components of mothers abuse by their adolescent children including: 1) Physical injury, 2) Emotional abuse; 3) Financial pressure, 4) The sense of being emotionally harmed, 5) Perception of child's behavior as an abusive interaction, 6) Spiritual harm, 7) Pathology, 8) Causality of abusive behavior; 9) Ambivalent perception of abusive behavior, 10) Cyclical nature of child-mother abusive interaction patterns, and 11) Intentionality of abusive behavior. Conclusion: The results of this study showed that the depth of harms to mothers abused by their adolescent children can be very extensive and severe. The insights from this study provide many contributions to counseling centers and family therapists.